2020
DOI: 10.1021/acs.bioconjchem.0c00166
|View full text |Cite
|
Sign up to set email alerts
|

Directing Quinone Methide-Dependent Alkylation and Cross-Linking of Nucleic Acids with Quaternary Amines

Abstract: Polyamine and polyammonium ion conjugates are often used to direct reagents to nucleic acids based on their strong electrostatic attraction to the phosphoribose backbone. Such nonspecific interactions do not typically alter the specificity of the attached reagent, but polyammonium ions dramatically redirected the specificity of a series of quinone methide precursors. Replacement of a relatively nonspecific intercalator based on acridine with a series of polyammonium ions resulted in a surprising change of DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The bQM cross-linking molecules also contain functional groups (R groups) that facilitate their association with DNA, which helps promote high cross-linking efficiencies (>85% with respect to number of DNA molecules modified). 75 Both an aromatic acridine 75 (Ac) and a trimer of positively charged quaternary amines 76 (N3) R groups have been studied. Here we will refer to these molecules generically as bQM(R) where R can be either the Ac or N3 group.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The bQM cross-linking molecules also contain functional groups (R groups) that facilitate their association with DNA, which helps promote high cross-linking efficiencies (>85% with respect to number of DNA molecules modified). 75 Both an aromatic acridine 75 (Ac) and a trimer of positively charged quaternary amines 76 (N3) R groups have been studied. Here we will refer to these molecules generically as bQM(R) where R can be either the Ac or N3 group.…”
Section: ■ Resultsmentioning
confidence: 99%
“…18−21 These reactive intermediates are typically formed transiently in vivo by oxidative or reductive metabolism of xenobiotics and drugs as illustrated most famously by the food preservative BHT 22 and the anticancer drugs mitomycin 23 and tamoxifen. 24 Synthetic QM precursors (QMP) have been developed for similar activation by oxidation 25,26 and reduction, 27,28 as well as by light, 19,29−31 hydrolysis, 32−34 desilylation, 35,36 and other mechanisms (Scheme 1). The highly reversible nature of certain QM-DNA conjugates also allows for generation of selfadducts that have been used to cross-link DNA at selected sequences without the need of an external signal.…”
Section: ■ Introductionmentioning
confidence: 96%
“…Quinone methides (QM) and related species are biologically relevant electrophiles that alkylate a variety of cellular nucleophiles including the nitrogens of DNA. These reactive intermediates are typically formed transiently in vivo by oxidative or reductive metabolism of xenobiotics and drugs as illustrated most famously by the food preservative BHT and the anticancer drugs mitomycin and tamoxifen . Synthetic QM precursors (QMP) have been developed for similar activation by oxidation , and reduction, , as well as by light, , hydrolysis, desilylation, , and other mechanisms (Scheme ). The highly reversible nature of certain QM-DNA conjugates also allows for generation of self-adducts that have been used to cross-link DNA at selected sequences without the need of an external signal. Similarly, a bisfunctional QMP conjugated to acridine (bisQMP, Scheme ) forms dynamic intrastrand cross-links that easily transform to interstrand cross-links (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Thermally or photochemically, QMPs have been reported to form quinone methides, and such reactive intermediates can alkylate amino acids, phosphodiesters, , and nucleic acids. , We have posited and then demonstrated that QMPs, as prodrugs for quinone methides, can resurrect the OP-aged form of AChE back to its native state. Such QMP compounds are not permanently charged and should allow for increased BBB penetrability over current pyridinium oxime therapeutics. Our hypothesis is that a QMP can reach the active site of the OP-aged cholinesterase and undergo quinone methide formation; furthermore, this active electrophile can realkylate the oxyanion of the phosphylated serine residue to generate a new inhibited enzyme form.…”
Section: Introductionmentioning
confidence: 99%
“…Thermally or photochemically, QMPs have been reported to form quinone methides, 40 and such reactive intermediates can alkylate amino acids, 41 phosphodiesters, 42,43 and nucleic acids. 44,45 We have posited and then demonstrated that QMPs, as prodrugs for quinone methides, can resurrect the OP-aged form of AChE back to its native state. 46−48 Such QMP compounds are not permanently charged and should allow for increased BBB penetrability over current pyridinium oxime therapeutics.…”
Section: ■ Introductionmentioning
confidence: 99%